Pelaksanaan Penetapan Lokasi Tanah Milik Masyarakat Untuk Pembangunan Kepentingan Umum - Edith Ratna M.S.; Sangga Yulia Sudrajat (Notarius, 2022)
The consideration of the implementation of this research is that there are problems that arise in land owners who are the object of land acquisition for development for the public interest, as a result of the provisions of Article 27 paragraph 3 of Law No.  2 of 2012 concerning Land Acquisition for Development for Public Interest, which is essentially "After determining the location of development for Public Interest, the Entitled Party can only transfer their land rights to the agency requiring land through the Land Agency".  Meanwhile, after the Determination of Location and the payment of compensation by the Government it takes a long time, under these conditions the community does not have certainty about their land ownership rights.  The results showed that: Land acquisition for the public interest according to the laws and regulations must be for the greatest prosperity of the people, carried out and owned by the Government, not for profit.  Its implementation according to laws and regulations is not entirely in line with the principles and objectives of Land Acquisition for Public Interest.  This research is a juridical-normative legal research, a qualitative form using secondary data consisting of primary legal materials.Keywords: land acquisition; public interest. AbstrakPertimbangan melaksanakan penelitian ini yaitu ada permasalahan di masyarakat pemilik tanah yang menjadi obyek pengadaan tanah sebagai onjek pembangunan untuk kepentingan umum, sebagai akibat dari Pasal 27 ayat 3 Undang-Undang Tahun 2012 No. 2 tentang Pengaadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum, yang intinya “Setelah penetapan lokasi pembangunan untuk Kepentingan Umum, Pihak yang Berhak hanya dapat mengalihkan hak atas tanahnya kepada Instansi yang memerlukan tanah melalui Lembaga Pertanahan”. Sementara itu, sesudah Penetapan Lokasi hingga pembayaran ganti rugi oleh Pemerintah memerlukan cukup lama waktu, dengan kondisi tersebut masyarakat tidak memperoleh kepastian tentang hak-hak kepemilikan tanahnya. Hasil penelitian memperlihatkan: Pengadaan tanah untuk kepentingan umum menurut hukum peraturan perundangan harus sebesar-besarnya untuk kemakmuran rakyat, dijalankan dan dimiliki oleh Pemerintah, tidak mencari keuntungan. Pelaksanaannya menurut peraturan perundangan tidak seluruhnya sesuai tujuan dan asas dari Pengadaan Tanah untuk Kepentingan Umum. Penelitian ini ialah penelitian hukum  yuridis-normatif, berbentuk kualitatif melalui penggunaan data sekunder yang mencakup bahan hukum primer.Kata Kunci : pengadaan tanah; kepentingan umum.